Chiral secondary amine catalyzed asymmetric cascade reactions - Dai, Lu (2012)
Enantioselective organocatalytic cascade reactions have attracted more and more attention during recent years. Chiral secondary amine catalyst played an important role in this kind of reaction. Hence three novel investigations of chiral secondary amine catalyzed asymmetric cascade reactions were developed.